2011
DOI: 10.1128/jvi.00056-11
|View full text |Cite
|
Sign up to set email alerts
|

ADP Ribosylation Factor 1 Activity Is Required To Recruit AP-1 to the Major Histocompatibility Complex Class I (MHC-I) Cytoplasmic Tail and Disrupt MHC-I Trafficking in HIV-1-Infected Primary T Cells

Abstract: HIV-1-infected cells are partially resistant to anti-HIV cytotoxic T lymphocytes (CTLs) due to the effects of the HIV Nef protein on antigen presentation by major histocompatibility complex class I (MHC-I), and evidence has been accumulating that this function of Nef is important in vivo. HIV Nef disrupts the normal expression of MHC-I by stabilizing a protein-protein interaction between the clathrin adaptor protein AP-1 and the MHC-I cytoplasmic tail. There is also evidence that Nef activates a phosphatidylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…8). This hypothesis is consistent with other studies demonstrating that dominant active ARF-1 mutants that hyperstabilize the Nef-MHC-I-AP-1 complex in T cells also inhibit MHC-I downmodulation by Nef (36). From these observations, we propose that efficient MHC-I downmodulation by HIV requires that Nef and/or AP-1 have the capacity to dynamically cycle off the affected molecules to recruit downstream proteins in the degradation pathway and to target the newly synthesized cargo molecules (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…8). This hypothesis is consistent with other studies demonstrating that dominant active ARF-1 mutants that hyperstabilize the Nef-MHC-I-AP-1 complex in T cells also inhibit MHC-I downmodulation by Nef (36). From these observations, we propose that efficient MHC-I downmodulation by HIV requires that Nef and/or AP-1 have the capacity to dynamically cycle off the affected molecules to recruit downstream proteins in the degradation pathway and to target the newly synthesized cargo molecules (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…By activating type Iα phosphatidylinositol-4-phosphate 5-kinase (PI4P5-K Iα) at virus-cell contact regions, HIV-1 is known to trigger the production of this PIP 2 -fusogenic lipid to promote fusion pore formation and viral infection [22], and the depletion of syntenin-1 allows a higher pool of free PIP 2 to accumulate at the plasma membrane after HIV-1 attachment [10]. Furthermore, PIP 2 -associated plasma membrane changes driven by Arf6 are crucial for early HIV-1 infection, ensuring cell surface regeneration when the virus fuses with and enters permissive cells [24,36,39]. It should be noted that gelsolin is regulated by both PIP 2 and intracellular Ca 2+ , which may represent additional control points for actin dynamics in the plasma membrane [20,32,40-43].…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies in HeLa or CEM-SS T cells, it has been reported that MHC-I is internalized into endosomal compartments coated with the small membrane associated GTPases ARF6 or ARF1 [33,34], which regulate membrane trafficking by inducing changes to actin dynamics. More research is needed to identify the specific membrane trafficking regulators mediating this process.…”
Section: Nef Promotes the Endocytosis Of Cell Surface Mhc-imentioning
confidence: 99%